Spiritual competency? (Journal of Parents and Teachers, 2012)
At first, the expression “Spiritual competency”, has characteristics in common with an oxymoron. First, because the spirit, sleepy or not, awaken or asleep, must be in everyone; and second, a spirit cannot be quantified and cannot be know from the outside.
Keywords: opinion; basic competencies; spiritual competency; philosophy and pedagogy.